Exploring multi-scenario simulation of ecosystem service value of Wetland in Yinchuan, China - Yuxuan, Gao; Muthuveeran, Adam Aruldewan S.; Mohd Yusof, Mohd Johari; Yali, Ma; Lulu, Ma (Human Resource Management Academic Research Society, 2023)
Wetlands have an important function in supporting urban biodiversity, regulating climatic patterns, and enhancing resilience against natural disasters. Wetland conservation in rural parts of western China is a matter of concern due to the presence of water scarcity, fragile ecosystems, and insufficient resilience to natural disasters. The objective of this project is to examine existing strategies or methods for conserving wetlands, investigate the most effective approaches to wetland conservation, and improve a simulation model that may be used to highlight the importance of wetland ecosystem services. This study aims to provide a theoretical framework to support the wetland conservation strategy, catering to the needs of both participants and policymakers involved in the process.